Performance of the ‘Anna’ apple (Malus domestica Borkh.) in Tropical Highlands: A review - Diego Alejandro Gutiérrez-Villamil; Javier Giovanni Alvarez-Herrera; Gerhard Fischer (Revista de Ciencias Agrícolas, 2022)
The 'Anna' apple is a variety of low requirements of winter chill (250 to 300 chilling hours ≤7.2°C). This apple has essential health benefits and remarkable adaptive potential in tropical and subtropical areas affected by climate change. Thus, this review presents the significance of the 'Anna' apple cultivation, the phenological and eco-physiological modifications, and the current state of agronomic management when continuous crops are managed in tropical highlands. The production of this apple in tropical highlands has outstanding potential to obtain cyclical or continuous harvests (two harvests per year) in certain areas with specific environmental conditions, implementing a particular management system. In plantations, it is crucial to carry out some agronomic practices during the reproductive phenology so that the apple tree does not enter into an endodormancy. These are water stress - defoliation - tie-down branches, and the application of dormancy-breaking agents (flower-inducing compounds). In Colombia, ‘Anna’ variety was introduced in 1985 and is grown in areas with temperatures between 14 and 20°C, altitudes between 1700 and 2800 meters above sea level (m a.s.l.), with bimodal and monomodal rain regimes, and solar brightness between 800 and 2000 hours a year. The harvest is between 100 to 120 days after anthesis, with firmness values of 38.38N, a soluble solids content of 8.58°Brix, and total titratable acidity of 0.7% of the fruit. This documentation indicates a good production with great potential in terms of growth and development, earliness, and quality of the 'Anna' apple tree in Colombian highlands.